2017
DOI: 10.3233/jad-161283
|View full text |Cite
|
Sign up to set email alerts
|

Google Calendar Enhances Prospective Memory in Alzheimer’s Disease: A Case Report

Abstract: We investigated whether an external memory aid (i.e., Google Calendar) would alleviate prospective memory compromise in a patient with mild Alzheimer's disease. The patient was asked in the baseline phase to perform three prospective targeted events (e.g., attending her weekly bridge game at the community club) and three prospective control events (e.g., buying her weekly magazine). The same six prospective events were assessed in the intervention phase but the targeted-events were cued by Google Calendar whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 45 publications
1
37
0
1
Order By: Relevance
“…A number of previously validated paper and pencil functional scales are also now available in online or mobile versions. Electronic organizer tools such as the Google Calender and AP@LZ have been tested in proof-of-concept studies with small samples to ameliorate functional and memory deficits, [17][18][19][20] which in turn may improve trial compliance. Figure depicts selected mobile or pervasive computing technologies that are being studied for use in AD research with examples in each area.…”
Section: Mobile Assessment Of Function (Activities Of Daily Living) Amentioning
confidence: 99%
“…A number of previously validated paper and pencil functional scales are also now available in online or mobile versions. Electronic organizer tools such as the Google Calender and AP@LZ have been tested in proof-of-concept studies with small samples to ameliorate functional and memory deficits, [17][18][19][20] which in turn may improve trial compliance. Figure depicts selected mobile or pervasive computing technologies that are being studied for use in AD research with examples in each area.…”
Section: Mobile Assessment Of Function (Activities Of Daily Living) Amentioning
confidence: 99%
“…With increasing emphasis on early detection and intervention for people with dementia, this study adds to the limited, but growing, body of literature suggesting the effectiveness of electronic memory aids for people with dementia. While this was the first piece of research evaluating the effectiveness of the MindMate app as a reminder tool, similar positive results have been reported with the Google Calendar app with both the ABI and dementia population (McDonald et al, 2011;Baldwin and Powell, 2014;El Haj et al, 2017).…”
Section: Efficacymentioning
confidence: 52%
“…Kinempt: Chang et., 2013); and table-setting (Giulio E. Lancioni et al 2009). Only one case report was identified investigating the effectiveness of an app (Google Calendar) with a participant with mild Alzheimer's disease (El Haj et al 2017). This study showed a reduction in forgetting of chosen target behaviours.…”
Section: Assistive Technology and Dementiamentioning
confidence: 98%
“…People with dementia often have difficulty performing daily activities owing to loss of memory and executive function [48]. Mobile technologies have been used as an external memory aid to help people with dementia remember future activities [25,26] and to provide visual and/or audio instructions for complex sequential tasks [29]. For step-by-step instructions, a context-aware system was used to detect situations or behavior through sensors in mobile devices [30,31] or clothing [30].…”
Section: Resultsmentioning
confidence: 99%